Prevalence of hip fracture in elderly people - Vásquez, Irene; Valenzuela, Cynthia; Zapata, Carola; Ruz, Samanta; Veronesi, Valeria; Iglesias, Verónica; Pino, Paulina (Revista Chilena de Salud Pública, 2005)
The aim was to establish the prevalence of hip fracture in the elderly residing in benefic institutions in Santiago city. A cross-sectional study of 200 institutional clinic records of interned >60 years selected by proportional stratified random sampling was performed. The prevalence of hip fracture was 9.5%. Women comprised 62.5% of the sample with ages averaging 81.9 + 8.8 whilst 37.5% were men with a mean age of 78.1 + 8.6. Conversely, the mean age of the fractured within the sample was 82.3 +/- 9.7 years. The main place of occurrence was the bathroom (26.3%) Prostration was the main sequel, increasing in 2.5% after the fracture. Mean weight and IMC were lower (p<0.05) in the fractured elders compared with those that did not experience fracture and the risk of fracture was mayor in those who had preview antecedents of fracture (RP 2.57; IC95% 1.1-5.8). The results contribute to the epidemiological knowledge of this pathology in the country though a hidden situation in non-registered institutions should be pointed out as a primary concern related to social and health equity. New studies are required to establish the prevalence in non-institutionalized population and to obtain a better understanding of the risk factors.